Harga diri pada pendukung pelaku hate speech di media sosial - Efi Lia Nurnanda (Cognicia, 2020)
Hate speech is a form of communication between individuals that involves denigrating, harrassing, intimidating or inciting hatred (provocation) towards individuals in certain groups or individuals, based on race, religion, gender or sexual orientation. The increase in cases of hate speech online makes researchers interested in conducting research on how the emergence of hate speech behavior in based on one of the factors, self-esteem. This study aims to analyze and describe self-esteem in hate speaker supporters on social media. This research incorporates a descriptive quantitative research model. The subjects of this study amounted to 149 people, aged 18-25 years who were selected using the accidental sampling technique. The research instruments in the present study are hate speech scale and self esteem scale. The results of this study indicate that hate speaker supporters tend to have a high level of self-esteem (52,3%) and moderate level of self-esteem (47,7%).